The complete mitochondrial genome sequence of Parabramis pekinensis strenosoma (Cypriniformes: Cyprinidae). (2nd January 2016) - Duan, Xiaoke; Zhang, Xiujie; Song, Wen; Wang, Yizhou; Gao, Zexia; Wang, Weimin
Abstract: Parabramis pekinensis strenosoma belongs to the family Cyprinidae. In the present study, we obtain the complete mitochondrial genome of P. pekinensis strenosoma by PCR amplification and DNA sequencing. It is a circular double-stranded DNA molecule of 16, 623 base pairs in length, consisting of the typical structure of 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, as well as 2 main non-coding regions (the control region and the origin of the light strand replication). Compared with Parabramis pekinensis, the two different subspecies share 99.58% nucleotide sequence similarity and the biggest nucleotide sequence discrepancy between homologous genes are observed in ND2 for protein-coding genes and in tRNA-Ala for tRNA-coding genes. The complete mitochondrial genome sequence data are of great use for phylogenetic analysis and studies of population genetics and germplasm resources of P. pekinensis strenosoma .